THE CORRELATION BETWEEN SELF CONFIDENCE IN SPEAKING SKILL AND ORAL PRESENTATION OF PBI UMY STUDENTS - Deshinta Wulan Purwandari (PBI 15 UMY 019, 2015)
*19 Oral presentation was one of acitivities given by teachers to their students as class assignment or final assessment. It had three important factors; delivery, self confidence, nervousness. Furthermore, this study only focused on the correlation between self confidence in speaking and oral presentation. This was quantitative study which involved 133 students of Pendidikan Bahasa Inggris (PBI) at Universitas Muhammadiyah Yogyakarta (UMY). Questionnaire was used to get data for dependent variable (self confidence in speaking skill) and students‟ oral presentation score was used to obtain the data for independent variable (oral presentation). Through SPSS version 20.0, this study found a positive correlation between self confidence in speaking skill and oral presentation with value 0.081. The strength value was 0.152 which indicated that the correlation is very low. The result showed that students always do practices before doing a presentation in order to reach the readiness point. When problems happened during their performance, such as when LCD suddenly did not work, they could overcome it. They had low anxiety in relation to making mistakes, being critized, and being shy. When those feelings came, they knew how to handle it. Moreover, students could focus on the material of the presentation regardless the situation. With the moderate level of self confidence, students could perform a very high skilled oral presentation.